Application of hill's strategy development framework on fast food restaurant business in Brunei Darussalam - Ringim, Kabiru Jinjiri; Ibrahim, Fahmi; Kura, Kabiru Maitama (2018)
This paper is an analysis of the Hill‟s Strategy Development Framework and application of the framework to a Fast Food Restaurant business which is operating in Brunei Darussalam.The study of this article concentrates on corporate objectives, marketing strategy, order qualifiers, order winners, and the operations strategy within the company.A review of the relevant literature conducted on corporate goals, competitive priorities, Order Qualifier and Order Winner. The methodology based on a desk review of secondary data and non-participant observations research approach.The findings demonstrated that Fast Food Restaurant Business in Brunei Darussalam required more considerable attention to focus on improving the Customer Service Relationship (CSR) value.It is crucial to concentrate on CSR that would enhance the business brand value, a better image rating and thereby contributing to company‟s sales and gaining a new customer.The study recommended that Fast Food Restaurant Business create a new market such as selling the frozen product.Fast Food Restaurant Business potentially can sell this in their store or export their patent right on the product internationally.The contribution of this paper is to provide provides a review of the application of the strategic framework to uncover the potential customer benefits package of the strategy.